Environmental risk assessment and stabilization/solidification of zinc extraction residue: I. Environmental risk assessment - Ozverdl, Arzu; Erdem, Mehmet (Elsevier, 2010)
The aim of this study was to determine environmental risks of zinc extraction residue. For this purpose; effects of pH. contact time and liquid/solid ratio on the leaching behaviors of the pollutants in the zinc extraction residue (ZER) were investigated in the batch leaching experiments and pollution potential of it was determined by toxicity characteristic leaching procedure (TCLP). synthetic precipitation leaching procedure (SPLP). multiple extraction procedure (MEP) and successive extractions Metal leachability tended to increase with decreasing liquid/solid ratio and pH. The concentrations of the metal leached exceeded the US EPA's toxicity characteristic threshold for Pb (5 mg/l) and Cd (1 mg/l). Also, Pb, Zn, Cd and Mn in the ZER leached above the drinking water standards thus possibly posing a potential risk to groundwater. It has been determined that the ZER is a solid waste having long-term pollution potential. (C) 2009 Elsevier B V. All rights reserved.
Keywords: Solid waste; Heavy metal pollution; Zinc; TCLP; MEP; SPLP